Evildoing: an attack on morality - Harrosh, S (2010)
This thesis presents a comprehensive theory of evildoing as an attack on morality, grounded in objective morality. It introduces evildoing as a distinct category of immorality, arguing that it is the relationship of evil acts to the core of morality that distinguishes them from ordinary wrongdoing. Two projects are undertaken: to provide an account of morality that can ground a theory of evildoing that is both objective and capable of systematically accommodating the diverse phenomena and definitions of evil acts, and to articulate and defend the attack on morality theory of evildoing. The challenge of the first project is met by a minimalist account of morality, structured by what I call the fundamentals of morality. The thesis defends a particular substantive account of these fundamentals, underpinned by the idea of conatus as the end of morality. Ultimately, it is conatus as the striving to persist in existence and prosper inherent in human beings that justifies the objectivity of the fundamentals of morality and with it the objectivity of the theory of evildoing, for it is these fundamentals that are attacked when we speak of an ‘attack on morality.’ Specifying and defending the conditions necessary for such an attack is the task of the second part of the thesis. An act constitutes evildoing, or an attack on morality, when it is wrong, results in serious harm to others, originates in an intention based on the correct belief that the act will cause or risk such harm, and where the perpetrator’s mental states and/or the act’s consequences are antagonistic to the realization of morality via one or more of its fundamentals.